Penal reform, anti-carceral feminist campaigns and the politics of change in women’s prisons, Victoria, Australia - Carlton, Bree (Punishment & society, 2018)
This paper emphasises the importance of locating contemporary abolitionist social movements within a continuum of broader struggles against structural injustice. Previous decades have seen the re-emergence of women’s penal reform programmes framed as progressive solutions for alleviating the structural disadvantages and harms associated with imprisonment. Abolitionists have provided fierce critiques of the risks these pose in reinforcing the legitimacy and scale of imprisonment. However, we have yet to articulate a clear vision regarding the utility of reform in relation to decarceration strategies. In presenting a critical exploration of anti-carceral feminist campaign work in Victoria, Australia, this paper advocates the need to move beyond the simplistically conceived dualism of reform and abolition. The analysis explores how anti-carceral feminists have used reform as a resistance strategy within Victorian anti-discrimination campaigns in the 1980s and 1990s. Placed in historical context, these campaigns demonstrate the transformative possibilities and risks associated with the necessary navigation and pursuit of reformist strategies that is fundamental to a politics and practice of abolition.